Evaluasi Pembelajaran PAI di Sekolah SMP Negeri 3 Bengkalis - Sazliana Sazliana; Sofia Rahmasari; Neliyanti Delsi; Siti Khairiah (JURNAL MANAJEMEN PENDIDIKAN, 2026)
EVALUATION OF PAI LEARNING AT STATE MIDDLE SCHOOL 3 BENGKALIS Evaluation in Islamic Religious Education (PAI) is an important component in measuring the success of the learning process and the overall development of students. This study is motivated by the importance of implementing evaluation that not only focuses on cognitive achievement but also encompasses affective and psychomotor aspects. The purpose of this research is to identify the forms of PAI learning evaluation covering cognitive, affective, and psychomotor domains at SMP Negeri 3 Bengkalis and to examine their implementation in the learning process. This study employed a descriptive qualitative approach with field research methods. Data were collected through observation, interviews, and documentation involving an Islamic Religious Education teacher and seventh-grade students at SMP Negeri 3 Bengkalis. The findings reveal that the evaluation of PAI learning has incorporated three assessment domains: the cognitive domain through written tests, assignments, exercises, and question-and-answer activities; the affective domain through observation of students’ attitudes, discipline, responsibility, and religious behavior; and the psychomotor domain through worship practices, Qur’an recitation, prayer memorization, and other religious skills. The study indicates that comprehensive evaluation across these three domains provides a more complete picture of student development and supports the achievement of Islamic Religious Education objectives. Therefore, PAI evaluation should be conducted continuously and integratively to develop students who are knowledgeable, morally upright, and skilled in practicing Islamic teachings.